Pengaruh Karakterisitik Masyarakat Terhadap Partisipasi Pemeliharaan Saluran Lingkungan di Desa Bandungrejo, Kecamatan Mranggen, Kabupaten Demak - Jatmiko, Yuhanto Ari (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
The provision of adequate environmental infrastructure on a settlement can not always be provided by the government because of the limited authority of the local government and the lack of resources and funding are owned by local governments. One of an effort that can be made relating to the maintenance of basic infrastructure and facilities is the involvement of public participation as a group of users who utilize direct the basic infrastructure and facilities. This study is aimed to look at the influence of society characteristics affecting the participation of neighborhood sewer maintenancein the Bandungrejo Village using correlation analysis of crosstab. Analysis of society characteristics and community participation carried out using quantitative methods to search for a number of variables that can be obtained from several reviews of a theory. From that variables then conducted a descriptive analysis of quantitative and analytical weighting. Based on field studies and processing questionnaire the results showed that the level of community participation in village Bandungrejo is still low. The characteristics of age, gender, occupation, income and education affect the participation of neighborhood sewer maintenance. In the case of the Bandungrejo village, variable length of stay has no effect because of economic factors and education dominate people's desire to participate more than other factors.